(untitled) (Latin American Journal of Sedimentology and Basin Analysis, 2020)
Fecal pellets and cysts of the brine shrimp Artemia (Crustacea, Branchiopoda, Anostraca) constitute an important component of the biogenic carbonate sedimentation in many saline and hypersaline lakes bodies. However, in Argentina there are not studies of its presence in the fossil record, being this paradoxical given the abundance of large and diverse endorheic salt basins existing in the country. In this study we present the morphological and petrographic characteristics of fecal pellets and cysts of Artemia sp. and its association with evaporitic minerals occurring in a sedimentary core covering the last ca.1300 years (1220 years cal. BP) from the Chasicó Lake (38 ° 37 ‘S; 63 ° 05’ W) (Fig. 1) discussing the potential of these indicators in paleoenvironmental studies. Taking into account the ecological requirements of this crustacean, the abundance of fecal pellets and cyst in the studied deposits is discussed in relation to the physical-chemical changes that occurred during that time. The sedimentary section was carried out considering the changes of texture, structure and color of the layers to select 18 sampling intervals (Fig. 2). The qualitative determination of the total sample was performed by X-ray powder diffraction analysis. The fecal pellets are white to dry light gray and are presented in elongated cylindrical sections (Fig. 3), with one end straight and another in blunt point. They have a maximum average length of 680 µm (Fig. 4; Table 1) with a rounded net edge. They consist of a carbonaceous sludge, with a darker core of organic matter and clay, an edge with an outer shell of authigenic carbonate in very small crystals (Fig. 5). In the impregnated sections, light and dark sheets were differentiated. In light sheets, pellets with ovoidal and elongated shapes are concentrated. In contrast, in the dark layers, the pellets are presented in a smaller proportion and are distributed in a weave of gray fibers of organic matter that would correspond to a microbial mat. The cysts are reddish with an average size of 232.36 ± 8.7 µm (Table 1, Fig. 3) and are entire, broken (open) and invaginated. A succession of siliciclastic mud (mostly formed by extrabasinal clastic components) and carbonaceous peloidal micritic-aragonitic mud with evaporites minerals (mostly intrabasinal chemical and biochemical components) was recognized. The sequence was divided into four units (Fig. 2): (1) Unit C: grayish green (5Y 3/1; 5 and 4/2, 5Y 5/4) laminated and disturbed micritic-aragonitic mud with halite and thenardite (76-143 cm); (2) Unit B: gray (10YR 6/1 and 10YR 4/2) disturbed massive micritic-aragonitic mud with thenardite (Na2SO4) (57-76 cm); (3) Unit A: gray (10YR 5/1) micritic-aragonitic laminates mud with halite and thenardite subordinate (20-57 cm); (4) Unit H: gray (10YR 5/1) siliciclastic and micritic massive mud with halite (0-20 cm) (Fig. 2). Artemia sp. fecal pellets and cysts were registered between ca. 730 AD and 1978 AD and are absent after ca. 1978 AD in the lacustrine deposits of Chasicó Lake. The sedimentary section (Fig. 2) showed a predominance of biochemical and chemical deposition and very little terrigenous material between ca. 730 AD and 1411 AD (units B and C), suggesting that the accumulation would have occurred far from the coastal margins and at depths equal to or greater than 3 m (Last, 1994). The increase of terrigenous material in some samples and the presence of lamination in unit A (subunit A1) (between ca. 1411 AD and 1978 AD) would also support that the deposition of this unit occurred in the central areas of the lake and would indicate the absence of both bottom currents (Eardley and Gvosdetsky, 1960) and seasonality in the deposition, with intervals with greater extra-basinal contribution. From ca. 1978 AD (unit H) there is an increase in the extra-basin contribution coinciding with the greater contributions from the Arroyo Chasicó water basin. The differences in mineralogy of evaporitic species associated with the presence of fecal pellets and cysts of Artemia sp. in units A, B and C, and the absence of pellets and cysts in unit H allowed recognizing four different stages that suggest net changes in the chemical environment of the lake during the last 1300 years (Fig. 2). Between ca. 730 AD and 1233 AD (unit C) there was a greater proportion of fecal pellets and cysts associated with halite and thenardite, the later as a stable phase of the mirabilite. This mineralogical association would reflect periods with high salinities (extreme hypersaline environments) that allowed the formation of halite and intervals of lower salinity (hypersaline environments) with deposition of sodium sulfate. Between ca. 1233 AD and 1411 AD (unit B) the presence of free thenardite from other salts suggests the formation of mirabilite as primary sulfate, which occurred during cold periods and salinity below the saturation index of halite. Deposits with thenardite, as the only evaporitic mineral, suggest lower salinities than in unit C that would have occurred during or after its deposition, which prevented the precipitation of chlorides. Coincidentally, a lower representation of Artemia sp. cysts was observed. From ca. 1411 AD to 1978 AD (unit A) the sequence presents sectors with lamination and abundant of fecal pellets of Artemia sp. and very thin to thin stratification (subunit A1, Fig. 2). The presence of halite suggests a significant increase in salinity over the entire period that allowed the sulfate to be in solution, or that its deposition occurred only in the form of mirabilite in coastal areas by cooling during winters. Between ca. 1978 AD and 2010 AD (unit H) fecal pellets and cysts of Artemia sp. are absent and halite is the only evaporitic mineral. This apparent contradiction would be explained by the formation of interstitial brine and an intrasedimentary precipitation of chloride, under current salinity conditions and not the salinity that corresponds to the deposition of muds. The absence of Artemia sp. was related to a reduction in salinity and the entry of predators to the lake, such as the pejerrey (Odontesthes bonariensis) that created unfavorable conditions for the reproduction and proliferation of Artemia sp. The presence and/or absence of fecal pellets and cysts of Artemia sp. showed a positive correlation with the increase and/or decrease in salinity in the lake with respect to the estimated values from precipitated salts. Inferences for the 20th century are supported by the historical and instrumental data from the Chasicó Lake. Taking into account that the cyst size is a biometric characteristic of the Artemia sp. species, this measure was used to assign the fossil cysts to A. persimilis, although specific determinations are necessary to ensure it. The presence of this native species before ca. 1978 AD and its subsequent absence suggests ecological reasons related to the effects of climate change that occurred since the end of 1970s and raises questions about the current biogeographic distribution of Artemia sp. in Argentina in relation to these changes.